Uji Organoleptik Dan Sifat Kimia Kue Semprong Campuran Tepung Ubi Jalar Ungu (Ipomoea batatas) Dan Tepung Terigu - Olfita S Montolalu; Tineke Langi; Teltje Koapaha (COCOS, 2019)
Sweet potato as a food ingredient, has a good quality in terms of nutritional content, especially carbohydrates, minerals, and vitamins. Processing purple sweet potato into flour is one way to store and preserve purple sweet potato. "Semprong" cakes traded in plastic packaging are generally made from flour with a variety of flavors and colors. Looking at the many variants of the "semprong" cake, this shows that the "semprong" cake can be combined with a variety of ingredients such as purple sweet potato flour. The aim of this research is to produce a quality semprong cake by mixing purple sweet potato flour and flour properly, based on the panelists' preference level and the nutritional characteristics of the "semprong" cake. This study uses a Completely Randomized Design (CRD) treatment A (10% purple sweet potato flour: 90% flour), B (30% purple sweet potato flour: 70% flour), C (50% purple sweet potato flour) : 50% white flour), D (70% purple sweet potato flour: 30% white flour), E (90% purple sweet potato flour: 10% white flour). The organoleptic test results of the "semprong" cake which are preferred in terms of color, taste, aroma and texture are treatment A (10g purple yam flour + 90g wheat flour). The results of the proximate content analysis of "semprong" cakes for water content ranged from 3.16% - 3.77%, ash content ranged from 1.32% - 2.09%, fat content ranged from 16.26% - 20.95%, content protein ranges from 7.06% - 8.95%, carbohydrate content ranges from 66.31% - 71.21%. Keywords : Semprong Cake, Purple Sweet Potato Flour and Wheat Flour